A Case Report on Diclofenac Induced Chronic Kidney Disease - Babladi, Vanishree Prakash; Patil, Neelkanthreddy; G, Manjunath; Salimath, Pooja V; Ninne, Sheetal R; Chary, K Mukteshwara (Indian Journal of Pharmacy Practice)
Non-steroidal Anti-inflammatory Drugs (NSAID) are one of the most commonly prescribed drugs and their nephrotoxic effects are well known. Diclofenac is one of the Non-steroidal anti-inflammatory drugs that exert anti-inflammatory, analgesic and antipyretic effects through the suppression of Prostaglandin (PG) synthesis, by inhibiting the enzyme Cyclooxygenase (COX). The most important mechanism of anti-inflammatory action of Non-steroidal anti-inflammatory drugs is considered to be inhibition of Cyclooxygenase-2 (COX-2) mediated enhanced prostaglandin synthesis at the site of injury. A 65-year male case was admitted with chief complaints of bilateral lower limb swelling and facial swelling. The patient history revealed that he had taken Tab. Diclofenac in combination with Paracetamol [acetaminophen] for almost one year. The final diagnosis was made as drug induced Chronic Kidney Disease (CKD), Hypertension (HTN), bilateral lower limb cellulitis and anemia. In this case, kidney disease and overuse of Diclofenac may account for the increase in blood pressure [hypertension]. The treatment was given accordingly after 7 days of hospital stay the patient had recovered and was given discharge.
Keywords: Non-steroidal anti-inflammatory drugs; Chronic kidney disease; Hypertension; Prostaglandin; Cyclooxygenase.